Hubungan Asupan Mineral Zinc, Tingkat Pendidikan Ibu dan Pendapatan Keluarga dengan Status Gizi Anak Sekolah Dasar - Putri Wardarita; Mohammad Zulkarnain; Achmad Fickry Faisyah; Rostika Flora; Nur Alam Fajar (Syntax Literate, 2021)
Zinc is a micronutrient in protein synthesis, cell differentiation and regulated growth for every cell in the body. Micronutrients such as zinc play a role in growth which affects the hormones that play a role in bone growth. Zinc deficiency can interfere with growth and development that is not optimal. This study aims to see the relationship between zinc mineral intake, mother's education level and family income with the nutritional status of elementary school children in Tuah Negeri, Musi Rawas District. This type of research used an observational study with a cross-sectional design. Sampling using simple random sampling technique. The number of samples is 75 respondents. Retrieval of data on the level of mother's education and family income with the interview method using a questionnaire. Data on the adequacy of zinc intake were carried out. SQ-FFQ interviews were asked about the amount of food in a questionnaire for the last period. Measurement of TB/u was carried out using anthropometry. The results of the statistical study showed that there was no relationship between the level of mother's education and the nutritional status of elementary school children (p = 1000). There was no relationship between zinc mineral intake and nutritional status in school children (p = 0.161). There is a close relationship with parents' income (p = 0.028) with the nutritional status of school children. The conclusion of this study is that children with a family income <UMR have the possibility of 4,327 times experiencing stuning.